Pendidikan Karakter Anak Berdasarkan Al-Qur'an Dan Hadits: Tanggung Jawab Orang Tua Di Era 5.0 - Nora Afnita; Syafruddin Syafruddin; Rehani Rehani; M. Sayuti; Andrianto Andrianto (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
The education of children plays a crucial role in influencing the values and principles of the future generation, particularly in the face of intricate contemporary issues. The goal of this research is to explore the significance of child education principles found in the Qur'an and Hadith, and how they can be applied in modern education. The research approach employed involves a literature review along with qualitative analysis, collecting information from sources such as the Qur'an, Hadith, and recent scientific publications on child education. The findings demonstrate that in the Islamic viewpoint, children's education places importance on qualities such as morals, knowledge, orderliness, empathy, and setting a good example, while also adapting to technological advancements and societal shifts. The conversation highlights the crucial role of parents and educators in establishing a supportive environment for children's education aligned with religious beliefs. The study's findings suggest that incorporating the teachings of the Qur'an and Hadith into children's education is crucial in cultivating a generation that is not only academically proficient but also possesses admirable character in the digital 5.0 age.